UTILIZING PODCASTS AS LEARNING MEDIA KD CERPEN FOR VISUALLY IMPAIRED STUDENTS - Reni Setiawati; Gunarhadi Gunarhadi; Tri Rejeki Andayani (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2022)
The use of podcasts as KD cerpen learning medium for visually impaired studentsaims to obtain learning media that is valid, practical and easy to understand and can be used for learning. The research method for using podcasts uses the ADDIE model. The ADDIE model consists of several stages, namely Analysis, Design, Development, Implementation, Evaluation. The data collection technique uses a validation sheet given to four validators, including validators for the feasibility of content (substance), presentation, language and graphics and media which aims to assess learning media. The results of the study showed that the acquisition of a content eligibility validation score (substance) was 3.55; presentation validation, namely 4.05; language validation is 3.77 and graphical and media validation is 4.38. So the overall average score of validating the use of podcasts as a medium for short story BC learning is 3.93 with a valid category. Learning media that have been valid are then tested on users. The test subjects were 2 visually impaired studentsof class VII SLB Negeri Salatiga.